Mitigating the Risks of Supporting Multiple Control Planes in a Production SDN Network: A Use Case - Bezerra, Jeronimo; Ibarra, Julio; Schwarz, Marcos; Freitas, Humberto; Morgan, Heidi (Anais do Workshop de Pesquisa Experimental da Internet do Futuro (WPEIF); 2017: Anais do VIII Workshop de Pesquisa Experimental da Internet do Futuro, 2017)
The SDN paradigm enables network operators to host multiple control planes in parallel, being an approach to support multiple network services. Supporting multiple control planes over production networks exposes the production environment to potential risks and increases operational complexity. To understand and mitigate these risks, we implemented procedures and tools that resulted in a more reliable network. This paper describes our experience and findings with the support of multiple control planes in a wide-area production network.